Numerical Analysis of the Inlet and Outlet Diameter Effects on Pulsation Dynamics and Cavitation in the Lobe Pump - H. Zhou; P. Zhou; L. Meng; J. Li; C. Xiang; H. Qian (Journal of Applied Fluid Mechanics)
To investigate the impact of inlet and outlet diameters on the performance of lobe pumps, this paper analyses six lobe pumps with an inlet and outlet diameter ratio of 1, as well as five lobe pumps with varying inlet and outlet diameter ratios, while keeping other conditions constant. Three-dimensional unsteady numerical simulations of the pumps were conducted using the full cavitation model and the re-normalization group (RNG) k-ε turbulence model. The results show that for the lobe pumps with internal diameters between 40 mm and 100 mm, the shaft power is reduced by 17.6%, the pressure is reduced by 0.4 MPa, the pulsation coefficient is reduced by 18%, the variation of the gas volume fraction at the gap is in the range of 0.2 to 0.8, and the maximum value of the radial force in the X-direction decreases from 58.36 to 17.6 kN, and that the maximum value of the radial force in the Y-direction decreases from 14.56 to 3.25 kN. When the scale is increased from 0.6 to 1, the shaft power decreases by 25.9%, the pressure decreases by 0.1 MPa, the pulsation coefficient decreases by 6%, the volume fraction of gas at the gap varies between 0.1 and 0.8, and the maximum radial force in the X-direction decreases from 17.63 to 12.52 kN, and in the Y-direction decreases from 7.68 to 6.32 kN. This shows that choosing a suitable inner diameter can reduce the cavitation tendency of the lobe pump, enhance its anti-cavitation ability, optimize the fluid flow characteristics, and thus improve its reliability and stability.